Spatial distribution of deaths due to Alzheimer’s disease in the state of São Paulo, Brazil - Almeida, Milena Cristina da Silva; Gomes, Camila de Moraes Santos; Nascimento, Luiz Fernando Costa (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Alzheimer’s disease is a common cause of dementia and identifying possible spatial patterns of mortality due to this disease may enable preventive actions. The objective of this study was to identify spatial distribution patterns of mortality due to Alzheimer’s disease in the state of São Paulo. DESIGN AND SETTING: Ecological and exploratory study conducted in all municipalities in the state of São Paulo. METHODS: Data on Alzheimer’s disease mortality in the state of São Paulo between 2004 and 2009 were obtained from DATASUS (the Department of Informatics in the Brazilian Ministry of Health). Death rates per 100,000 inhabitants were then calculated and spatial analysis was performed by constructing a death rate map, global Moran index and local Moran index, which were used to obtain the Moran map. The kernel technique was also applied. The Terra View 4.0.0 software was used. RESULTS: 13,030 deaths due to Alzheimer were reported in the state of São Paulo (rate of 5.33 deaths/100,000 inhabitants). São José do Rio Preto, Ribeirão Preto, Bauru and Araçatuba had higher rates. The Moran index was I = 0.085 (P < 0.002). The Moran map identified 42 municipalities that merit intervention and the kernel estimator identified a high density of deaths in the northwestern region of the state. CONCLUSION: Higher densities of deaths due to Alzheimer were concentrated more to the north and northwest of the state of São Paulo. It was possible to identify municipalities that have priority for interventions to reduce the death rates due to this disease.